Implementasi Pembelajaran Tematik dalam Meningkatkan Hasil Belajar Siswa di SDN 102 Pudukku - Ampallang Ampallang; Izharuddin Harun (Mahaguru: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
The problem discussed in this study is how to implement thematic learning in improving student learning outcomes at SDN 102 Pudukku. The purpose of this study was to determine the implementation of thematic learning in improving student learning outcomes at SDN 102 Pudukku. This research is a field research with a qualitative descriptive approach, namely describing and interpreting according to the data obtained. Primary data sources are data sources which are the main data sources in this study, which were obtained from school principals, study teachers at SDN 102 Pudukku in the field of Islamic Religious Education, Mathematics, Social Sciences (IPS), Natural Sciences (IPA), Indonesian Language, Citizenship Education, Physical Education, and other educators. Data collection techniques used are observation, interviews, and documentation. Data analysis techniques using qualitative data analysis were carried out interactively through the process of data reduction, data display, conclusion drawing/verification. The conclusion in improving student learning outcomes at SDN 102 Pudukku is that it has not gone well, this is due to a lack of socialization about thematic learning, the teacher's lack of understanding of thematic learning explanations in the curriculum used, the lack of information obtained by the teacher to carry out thematic learning, there is no guide for teachers to be able to develop learning to be thematic, and teachers cannot develop it in the form of themed lesson plans.